Travelling Salesman Problem in The Case of Refined Sugar Shipment From Distribution Centers For the beverage Industries - Ratna Ekawati; Yandra Arkeman (Journal Industrial Servicess, 2020)
Travelling Salesman Problem (TSP) is one of the route management models with a higher level of complexity than the shortest path problem (SPP). In the logistic context, the distribution of products can be in the form of resources such as trucks, ships, aircraft, and other transportation fleets that can be completed with different settlement models. In TSP, researchers look for the shortest route that crosses all cities the product will be sent to and will end up in the city that first sent the product. The distribution of refined sugar that occurs is a problem that is not following its designation, causing the proposed creation of a distribution center to streamline the distribution of refined sugar to a beverage company that is closest to the processing plant and its delivery with the same truck trailer. with more structured through the formulation of a linear program for TSP with asymmetrical distance matrix. So that resulting in minimizes the distance distribution of refined sugar by trucks in distributing its products by 74.28%.